누룽지의 향기성분 분석을 위한 추출방법 비교 - 황지선(Ji-sun Hwang); 이주연(Juyeon Lee); 김미나(Mina K. Kim) (한국식품과학회지, 2024)
본 연구에서는 누룽지의 향기성분 분석 시 추출방법에 따른 향기성분의 특성을 비교하였다. DRP법 및 SAFE법으로 확인한 누룽지의 휘발성 향기성분은 총 8종이었으며, 각 추출방법별로 7종의 성분이 확인되었다. 또한 SAFE법 대비 높은 압력, 가열 온도와 추출 시간이 필요한 DRP법에서 더 많은 양의 향기성분이 나타나는 것을 확인하였다. 이를 토대로 하여 누룽지의 향기성분동정 시 적절한 추출방법을 확립하여 향후 누룽지의 향기성분에관한 연구에 활용할 수 있을 것이라고 생각된다. Nurungji is a traditional rice-based snack that is widely consumed in Korea. The purpose of this study was to compare two volatile aroma compound extraction methods for Nurungji flavor analyses, namely steam distillation under reduced pressure (DRP) and solvent-assisted flavor evaporation (SAFE). Once extracted, extracts were analyzed qualitatively and quantitatively via stir bar sorptive extraction by gas chromatography-mass spectrometry (SBSE-GC-MS). Eight compounds were isolated using the two extraction methods, and seven compounds were separated via the DRP method and the SAFE method. From the results of the two extraction methods, the concentrations of four compounds, including hexamethyl cyclotrisiloxane, 2,4-decadienal, nonanal, and butyl isobutyl phthalate, were measured and were significantly different (p<0.05). Between these two extraction methods, more aromatic compounds were extracted with the DRP method than with the SAFE method. KCI Citation Count: 0